Structural optimization of nanofluid flow around an equilateral triangular obstacle. (August 2015) - Rashidi, S.; Bovand, M.; Abolfazli Esfahani, J.
Abstract: Convective heat transfer of Al2 O3 –water nanofluid over an equilateral triangular obstacle with an optimization analysis is carried out to determine the optimum conditions for the maximum heat transfer rate and the minimum drag coefficient. Orientations of the obstacle, values of the solid volume fraction, and Reynolds number are selected as the input parameters. The analysis is performed according to the Response Surface Methodology. The response surface equation is obtained using the design of the experiments features. Two-dimensional unsteady equations with the relevant boundary conditions have been solved using finite volume method. Three different orientations of the triangular obstacle are defined for the optimization procedure. The computational simulations are done for different Reynolds numbers ( 1 ≤ Re ≤ 180 ), solid volume fractions ( 0 ≤ φ ≤ 0.05 ) and orientations of the triangular obstacle ( 0 ° ≤ θ ≤ 60 ° ). Also, a comparison is performed between the results of CFD analysis and Response Surface Methodology. It is found that the minimum drag coefficient is occurred at θ = 35.13°, Re = 97.6 and φ = 0.01 and the maximum Nusselt number is found at θ = 8.49°, Re = 180 and φ = 0.05. Graphical abstract: Highlights: The optimum conditions for maximum heat transfer and minimum drag are investigated. A comparison is performed between the numerical and optimization results. The minimum drag coefficient is occurred for θ = 35.13, Re = 97.6 and φ = 0.01. The maximum Nusselt number is for θ = 8.490, Re = 180 and φ = 0.05. The Nusselt number is more sensitive to the angle rather than the drag coefficient.